Effect of fiber configuration on the fiber-to-mortar bond behaviour - Esfahani, Ali Dalalbashi (2019)
Textile-reinforced mortar (TRM) composites have received extensive attention as a sustainable solution for seismic strengthening of masonry and historical structures. This new system is composed of textile fibers embedded in an inorganic matrix and is applied on the masonry substrate surface as an externally bonded reinforcement (EBR) system. The bond at the textile-to- mortar and at the mortar-to-substrate interfaces are the main stress-transfer mechanisms and therefore should be thoroughly investigated. Although several studies have been focused on characterization of the bond behavior in MRT- masonry composites during the last years, there is still a lack of suitable constitutive laws. Most of the available studies have addressed the bond behavior through single-lap shear bond tests in which the bond of the MRT system to masonry substrate is evaluated. The bond performance between the fiber and mortar, however, has received few attention and is the main subject of this study. The presented work consist of fiber pull-out tests on a (unidirectional) steel-based and a (bidirectional) glass-based TRM composite as common reinforcing systems. The roles of transverse fibers (in glass-based TRM) as well as number of fibers on the bond behavior are also investigated. The results show that transverse elements cause toughness to increase. In addition, by increasing the number of fibers, the obtained failure modes change from slipping to mortar cracking.